Zakaz sponsorowania przez podmioty branży tytoniowej - Balwicka-Szczyrba, Małgorzata; Balwicki, Łukasz (Kwartalnik Prawa Publicznego, 2013)
In accordance with Article 8 Paragraph 2 of the Act of 9.11.1995 on the protection of health against the consequences of tobacco use and tobacco products, tobacco company sponsorship of sporting activities, cultural, educational, health and socio-political is prohibited. The article discusses the subjective and objective scope of that ban in relation to ratified by Poland the Framework Convention on World Health Organization’s Tobacco dated 21.5.2003, and Directive No. 2003/33/EC of the European Parliament and of the Council dated 26.5.2003 on the approximation of laws, regulations and administrative provisions of the Member States relating to the advertising and sponsorship of tobacco products.